Operative Vaginal Birth of a Critically Endangered Gorilla With Forceps Assistance. Issue 1 (July 2020) - Monseur, Brent; McCurdy, Rebekah; Ialeggio, Donna; Hinshaw, Keith; Georoff, Timothy; Weiner, Stuart
Abstract : BACKGROUND: An obstetrician on standby assessed an 18-year-old primiparous captive gorilla with a term singleton fetus with a protracted labor course. CASE: After it was determined that an arrest of descent had occurred, a viable, 2, 280 g male neonate was delivered through an operative vaginal birth with forceps assistance without major complications. CONCLUSION: Given the numerous anatomic and biochemical similarities of humans and other great apes, it is possible that the high maternal mortality and stillbirth rates of gorillas could be reduced by using the same principles of obstetric management in a multidisciplinary fashion. Abstract : Active management of dystocia using obstetric forceps is an important technique to prevent stillbirth and primary cesarean birth in nonhuman great apes.